Speed Estimation of DTC Induction Motor Using Single Current Sensor Based on Wavenet Theory - Alwan, Majid A.; Abdul-Jabbar, Jassim M.; Obed, Adel Ahmed (Basrah Journal for Engineering Sciences, 2008)
In this paper induction motor and its direct torque control are simulated and a speed estimator scheme based on wavenet (WN) theory has been developed and compared with the actual speed. The wavenet speed estimator inputs are a single line current and the state of the torque comparator output which are trained to follow the relationship between the motor current and the rotor speed. To ensure the validity of this scheme, the estimated speed is compared with a speed estimated from a conventional model reference adaptive system (MRAS). The operation of direct torque control (DTC) drive with the actual speed and the estimated wavenet speed as a feedback signal are simulated and compared. The results show that the wavenet method is effective for rotor speed estimation.